Visualizing Population Dynamics of Alaska’s Arctic Communities - Hamilton, Lawrence C.; Mitiguy, Angela M. (ARCTIC, 2009)
Arctic demography has previously been reviewed on a large scale, across the circumpolar nations. We look instead at some recent population dynamics on sub-regional to community scales, focusing on Arctic Alaska. Detailed graphics depicting yearly population changes from 1990 to 2006 in 43 selected Arctic Alaska towns and villages and all 27 of the state’s “county-equivalent entities” (e.g., boroughs) have been published online in connection with two International Polar Year projects. Seemingly comparable places within the same borough have taken widely divergent paths. Birth rates generally exceed death rates, although both are high. Year-to-year and place-to-place variations are dominated not by natural increase, but by differences in net migration. Population changes influence demand for resources such as water, electricity, fuel, and capital improvements, and probably for subsistence resources as well. Migration rates provide sensitive indicators that integrate diverse internal and external pressures. La démographie de l’Arctique a déjà été étudiée à grande échelle, soit à la grandeur des nations circumpolaires. Ici, nous examinons plutôt certaines des récentes dynamiques de population de l’échelle sous-régionale à l’échelle communautaire, en nous concentrant sur l’Alaska de l’Arctique. Des graphiques détaillés illustrant les changements de population annuels de 1990 à 2006 dans 43 villes et villages choisis de l’Alaska de l’Arctique ainsi que dans tous les 27 « entités équivalant à des comtés » de l’État (des arrondissements par exemple) ont été publiés en ligne dans le cadre de deux projets de l’Année polaire internationale. Des endroits de toute apparence comparables au sein du même arrondissement ont pris des airs très divergents. Généralement, les taux de natalité dépassent les taux de mortalité, quoique les deux soient élevés. Les écarts d’une année à l’autre et d’un endroit à l’autre ne sont pas dominés par l’accroissement naturel mais plutôt par les différences caractérisant la migration nette. Les ...